Monetary Policy in an Equilibrium Portfolio Balance Model - Kumhof, Michael (IMF Working Papers; Working Paper ;, 2007)
Standard theory shows that sterilized foreign exchange interventions do not affect equilibrium prices and quantities, and that domestic and foreign currency denominated bonds are perfect substitutes. This paper shows that when fiscal policy is not sufficiently flexible in response to spending shocks, perfect substitutability breaks down and uncovered interest rate parity no longer holds. Government balance sheet operations can be used as an independent policy instrument to target interest rates. Sterilized foreign exchange interventions should be most effective in developing countries, where fiscal volatility is large and where the fraction of domestic currency denominated government liabilities is small.